Analisis Pertumbuhan Return On Investment (ROI) pada PT. Kino Indonesia Tbk Sebelum dan Sesudah Go Public - Danna Solihin3, Annisa Setiyo Wati1 Mardiana 2 (EKONOMIA, 2020)
Annisa Setiyo Wati, Analysis of Return On Investment (ROI) at PT. Kino Indonesia Tbk Before and After Go Public (under the guidance of Ms. Mardiana as advisor I and Mrs. Danna Solihin as mentors II). The purpose of this study is to know and analyze the growth of PT. Kino Indonesia Tbk Return On Investment (ROI) before and after going public.The theoretical basis used in this study is Sujarweni (2016:6) argues that the definition of management accounting is